2020
DOI: 10.3390/nu12061879
|View full text |Cite
|
Sign up to set email alerts
|

Patients Undergoing Myeloablative Chemotherapy and Hematopoietic Stem Cell Transplantation Exhibit Depleted Vitamin C Status in Association with Febrile Neutropenia

Abstract: Patients undergoing myeloablative chemotherapy and hematopoietic stem cell transplantation (HSCT) experience profound neutropenia and vulnerability to infection. Previous research has indicated that patients with infections have depleted vitamin C status. In this study, we recruited 38 patients with hematopoietic cancer who were undergoing conditioning chemotherapy and HSCT. Blood samples were collected prior to transplantation, at one week, two weeks and four weeks following transplantation. Vitamin C status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
(47 reference statements)
1
26
0
Order By: Relevance
“…Vitamin C supplementation is being explored as an adjuvant to many existing cancer therapies (Figure 3B). As cancer patients frequently present with decreased plasma vitamin C levels (Waldo and Zipf, 1955;Anthony and Schorah, 1982;Mayland et al, 2005;Carr et al, 2020) that are further FIGURE 3 | Vitamin C uptake and therapeutic potential as an anti-cancer agent. (A) Structures of ascorbate (ASC) and dehydroascorbate (DHA).…”
Section: Effect Of Vitamin C Treatment As An Anti-cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin C supplementation is being explored as an adjuvant to many existing cancer therapies (Figure 3B). As cancer patients frequently present with decreased plasma vitamin C levels (Waldo and Zipf, 1955;Anthony and Schorah, 1982;Mayland et al, 2005;Carr et al, 2020) that are further FIGURE 3 | Vitamin C uptake and therapeutic potential as an anti-cancer agent. (A) Structures of ascorbate (ASC) and dehydroascorbate (DHA).…”
Section: Effect Of Vitamin C Treatment As An Anti-cancer Therapymentioning
confidence: 99%
“…Mild vitamin C deficiency may be underreported owing to its non-specific symptoms such as fatigue, irritability, dull aching pains, and weight loss ( Prinzo, 1999 ; Schleicher et al, 2009 ). All-cause mortality decreases when vitamin C serum levels rise above 60 μM ( Goyal et al, 2013 ; Wang et al, 2018 ), while in cancer patients, low serum vitamin C levels of <20–30 μM are frequently observed ( Waldo and Zipf, 1955 ; Anthony and Schorah, 1982 ; Mayland et al, 2005 ; Carr et al, 2020 ). A study of leukocytes isolated from colon cancer patients showed decreased levels of 5mC and 5hmC that correlated with blood plasma ascorbate below 20 μM, while expression of TET genes was not significantly changed ( Starczak et al, 2018 ).…”
Section: Vitamin C Deficiency and Effects On Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ascorbate deficiency was able to cooperate with Flt3 ITD to promote leukemogenesis in a manner similar to Tet2 loss. 52 A number of studies have found that patients with hematologic cancers are ascorbate deficient, [53][54][55] and these patients are likely to have decreased TET2 activity even in the absence of TET2 mutations.…”
Section: Context 1 Heterozygous Mutations In Tet2mentioning
confidence: 99%
“…Cancer research: Dr Wang and colleagues have identified key molecular targets of vitamin C activity in triple-negative breast cancer metastasis in cell culture and a xenograft model [ 7 ], indicating that vitamin C can potentially inhibit metastasis by modulating the expression of SYNPO2 and YAP1. Observational research by Carr and colleagues has indicated that patients undergoing chemotherapy in association with stem cell transplantation exhibit depleted vitamin C status in association with febrile neutropenia [ 8 ]. Further observational research by Dachs and colleagues indicated that low vitamin C status in patients with cancer is associated with both patient and tumor characteristics [ 9 ].…”
mentioning
confidence: 99%